Dual-indentation technique for the assessment of strength properties of cohesive-frictional materials - Constantinides, Georgios; Ganneau, F. P.; Ulm, Franz Josef (My University, 2006)
We propose a dual indentation technique for the assessment of the cohesion and friction angle of cohesive-frictional materials of the Mohr-Coulomb type. The technique is based on a computational implementation of the yield design theorems applied to conical indentation tests with different apex angles. The upper bound solutions are found to be very close to flat indentation solutions available for cohesive-frictional materials. On this basis we derive fundamental hardness-to-cohesion solutions in function of the friction angle and the apex angle. By studying the property of these dimensionless relations, we show that the ratio of two hardness measurements obtained from indentation tests with different apex angles, allows one to determine the friction angle. This dual indentation method is applied to Berkovich and Corner Cube indenter assimilated to equivalent cones of different apex angle. The method is validated for a 'model' material, metallic glass, which has recently been identified as a cohesive-frictional materials. The only input to the method are two hardness values which we obtain by microindentation on metallic glass. The outcome are values of the cohesion and friction angle, which are found to be in excellent agreement with reported cohesion and friction angle values of metallic glass obtained by macroscopic triaxial testing and comprehensive finite-element backanalysis of indentation curves.
Keywords: Hardness; Finite element method; Metallic glasses; Strength of materials